Modeling of human neurulation using bioengineered pluripotent stem cell culture - Xue, Xufeng (Curr Opin Biomed Eng, 2020)
Leveraging the developmental potential and self-organizing property of human pluripotent stem (hPS) cells, researchers have developed tractable models of human embryonic development. Owing to their compatibility to live imaging, genome editing, mechanical perturbation and measurement, these models offer promising quantitative experimental platforms to advance human embryology and regenerative medicine. Herein, we provide a review of recent progress in using hPS cells to generate models of early human neural development or neurulation, including neural induction and regional patterning of the neural tube. These models, even in their nascent developmental stages, have already revealed intricate cell-cell signaling and mechanoregulation mechanisms likely involved in tissue patterning during early neural development. We also discuss future opportunities in modeling early neural development by incorporating bioengineering tools to control precisely neural tissue morphology and architecture, morphogen dynamics, intracellular signaling events, and cell-cell interactions to further the development of this emerging field and expand its applications.